Study of the Interface between Rhodium and Carbon Nanotubes - Suarez-Martinez, Irene; Ewels, C.; Ke, X.; Van Tendeloo, G.; Thiess, S.; Drube, W.; Felten, A.; Pireaux, J.; Ghijsen, J.; Bittencourt, C. (American Chemical Society, 2010)
X-ray photoelectron spectroscopy at 3.5 keV photon energy, in combination with high-resolution transmission electron microscopy, is used to follow the formation of the interface between rhodium and carbon nanotubes. Rh nucleates at defect sites, whether initially present or induced by oxygen-plasma treatment. More uniform Rh cluster dispersion is observed on plasma-treated CNTs. Experimental results are compared to DFT calculations of small Rh clusters on pristine and defective graphene. While Rh interacts as strongly with the carbon as Ti, it is less sensitive to the presence of oxygen, suggesting it as a good candidate for nanotube contacts.